THE EFFECT OF PERCEPTION AND MOTIVATION ON TAX CONCENTRATION STUDENTS 'INTEREST FOR A CAREER IN TAXATION - Tenriwaru Tenriwaru; Amiruddin Amiruddin; Nurfadilah Nurfadilah (JOSAR (Journal of Students Academic Research), 2016)
This study aims to determine the effect of perceptions about taxes and student motivation for tax concentration for a career in taxation. The variables in this study are Perception (X1), Motivation (X2) and Interest (Y). This type of research used in this research is quantitative. The data collection technique is done by using a questionnaire. The population of this study was students of taxation concentration. The method used to determine the sample is purposive sampling method. Data analysis was performed using multiple linear regression analysis. The results of the research partially and simultaneously show that perception and motivation have a positive and significant effect on student interest in tax concentration for a career in taxation.